Islamic Religious Education Learning Strategies in Shaping the Religious Character of Grade III Students - Usmayanti, Yanti; Said, Basnang (Jurnal Iman dan Spiritualitas, 2025)
This study analyzes Islamic Religious Education (PAI) learning strategies in shaping the religious character of third-grade students at SDN Emo Kurniaatmaja through a qualitative case study approach. The objectives of the study were to identify learning strategies, evaluate their effectiveness, and analyze supporting and inhibiting factors in the formation of religious character. Data were collected through participant observation of 12 learning sessions, in-depth interviews with 3 PAI teachers and 25 students, and analysis of curriculum documents and Lesson Implementation Plans (RPP). The results showed that contextual-based strategies—such as bullying simulations to instill tolerance values ​​and direct practice of distributing takjil—increased student participation by 78%. The role of teachers as spiritual role models (34%) and habituation of worship (29%) were the dominant factors in the predictive model of religious character. Although the PAI time allocation was only 2 hours/week, the integration of hidden curriculum such as calligraphy of Quranic verses on classroom walls successfully strengthened the internalization of values. The study's conclusion confirms that a holistic strategy design that combines teacher role models, contextual learning, and school system support can optimize the formation of religious character in public elementary schools with limited time. These findings suggest that teacher training should be based on Islamic personality competencies and that the Islamic Education (PAI) time allocation policy should be revised to be more flexible.